CPC-123 Risperidone and Suspected Angioneurotic Oedema: Contribution of Multidisciplinary Care. (12th March 2013) - Agullo, M; Duffy, S; Thanh, A Du; Villiet, M; Esteller, S Hansel
Abstract : Background: Psychotropic drugs may cause cutaneous eruptions with various degrees of severity ranging from urticaria to 'angioedema' (AE). Respiratory tract obstruction needs emergency care. Purpose: To report on a patient who developed facial AE following treatment with risperidone. Materials and Methods: An 85-year-old woman was admitted to the emergency department (ED) for acute respiratory failure 24 hours after risperidone was introduced. Results: She presented macroglossia, dyspnoea and oedema of the soft palate, unresolved with antihistamines and steroids. In the ED, risperidone was reintroduced for agitation. It was immediately followed by severe dyspnoea, oedema of the tongue and uvula requiring admission to the intensive care unit. Risperidone imputability was suspected after a review of the literature. The Regional Reference Centre for Bradykinin AE (BAE) was consulted. Allergic oedema caused by risperidone but not BAE was concluded (delay of occurrence, absence of real BAE case with risperidone). Risperidone was stopped, the patient was monitored and treated with the optimal dose of steroids and antihistamines. Oedema resolved in 48 hours and patient went back home without sequelae. Naranjo evaluation scored 9, so it was highly probable that oedema was linked to the drug. Conclusions: AE can result in laryngeal oedema and fatal airway obstruction. When differential diagnoses are eliminated, AE is classified into allergic/pseudo-allergic or bradykinin-related (hereditary or acquired with angiotensin-converting enzyme inhibitors and sartans). The mechanism of drug-induced BAE seems to be mediated by increased plasma bradykinin levels, because these drugs reduce its breakdown. AE has been reported to occur with antipsychotics like risperidone, but these drugs probably produce histaminergic AE, not BAE. In our case, this hypothesis must be ruled out with cutaneous allergology prick tests with risperidone. Diagnosis of BAE can be difficult. Clinical signs and oedema resistant to conventional treatments have led to suspicion of BAE. French Reference Centres can improve and optimise detection and treatment of these orphan diseases and limit use of expensive drugs ( e.g. icatibant: 6, 300 US dollars per patient). No conflict of interest.